Radar polarization data analysis for safe navigation under the condition of hail zones - Браун, І.М.; Яновський, Ф.Й. (Proceedings of National Aviation University (archive), 2005)
The paper is devoted to analysis of experimental sensing data of clouds and precipitation by microwave radars and their comparison with theoretical models. As a result, a features set of polarimetric variables, which are necessary as a priori data for synthesis of processing algorithms of radar signals, is formed with the purpose to solve various applied problems, in particular, hail recognition for flight safety and air traffic control.